Beneficial effects of 1,3–1,6 β-glucans produced by Aureobasidium pullulans on non-esterified fatty acid levels in diabetic KKAy mice and their potential implications in metabolic dysregulation - Ikewaki, Nobunao; Ikeue, Yasunori; Nagataki, Mitsuru; Kurosawa, Gene; Dedeepiya, Vidyasagar Devaprasad; Rajmohan, Mathaiyan; Vaddi, Suryaprakash; Senthilkumar, Rajappa; Preethy, Senthilkumar; Abraham, Samuel J. K. (Journal of diabetes and metabolic disorders, 2023)
Objectives In this study, we used an obese and diabetic mouse model to compare two strains of Aureobasidium pullulans (AFO-202 and N-163) produced beta-glucans (β-glucans), which alleviate lipotoxicity. Methods Four groups of KK-Ay mice were used, with six subjects in each group. Group 1: sacrificed on day 0 for baseline values; Group 2: control (drinking water); Group 3: AFO-202 beta glucan—200 mg/kg/day; Group 4: N-163 beta glucan—300 mg/kg/day for 28 consecutive days. Results Group 4 (N-163) had the lowest non-esterified fatty acids (NEFA) levels and marginally decreased triglyceride levels compared to the other groups. There were no significant differences in blood glucose, hemoglobin A1c (HbA1c), triglycerides, low-density lipoprotein (LDL), and high-density lipoprotein (HDL) cholesterol levels. N-163 β-glucans decreased NEFA levels after 28 days. Conclusion These results, although modest, warrant further in-depth research into lipotoxicity and associated inflammatory cascades in both healthy and diseased subjects for the prevention and management of metabolic dysregulation and associated diseases such as non-alcoholic fatty liver disease (NAFLD).